The Influence of Viral Marketing and Celebrity Endorser Song Joong Ki on Consumers Purchase Intention of Scarlett Whitening Skincare Products in Jakarta - Ruslim, Christina Ellena; Setyaningsih, Rita Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Nowadays, beauty products are increasingly diverse and growing many local brands are constantly emerging with various types. So that a new promotion method emerged, namely viral marketing and celebrity endorsers. Therefore, this research will specifically discuss viral marketing and celebrity endorsers to find out consumers purchase intentions towards Scarlett Whitening skincare products. The theories used in this study are viral marketing, celebrity endorsers, and purchase intentions. The independent variables in this study are viral marketing and celebrity endorsers, while the dependent variables in this study are purchase intentions. The object of this study is the skincare product Scarlett Whitening. Data collection was carried out by distributing questionnaires to 100 samples of male and female consumers aged at least 17 years and over who had seen advertisements for Scarlett Whitening skincare products on Instagram. Sampling is carried out by means of non-probability sampling with judgment sampling techniques. The data of this study were processed using SPSS 25. The results of this study are (1) viral marketing has proven to have a positive and significant effect on consumers' purchase intentions of Scarlett Whitening skincare products in Jakarta and (2) celebrity endorsers have been shown to have a positive and significant effect on consumers purchase intentions of Scarlett Whitening skincare products in Jakarta.